CLINICAL OUTCOMES OF GONARTHROSIS TREATMENT IN ELDERLY AND SENILE PATIENTS AND THEIR EVALUATION - Allokulov Rustam Ruzibaevich; Akramov Vohid Rustamovich (Uzbekistan Open Conference, 2025)
The article used conservative and surgical methods of treating gonarthrosis in elderly and aged patients, the choice of which depended on the stage of the disease and the severity of clinical symptoms. Conservative treatment was performed in the initial stages of gonarthrosis. Surgical treatment was performed at stages II-III and III-IV of the disease with the continuation of conservative treatment. A non-drug treatment regimen for patients with diagnosed gonarthrosis was developed, physical conditions were limited, reducing the impact of dynamic and static factors directly affecting the knee joint.
Keywords: gonarthrosis; elderly and aged patients; surgical and non-drug treatment